MICROCYSTIN-LR ATTENUATES BLOOD CALCIUM AND PHOSPHATE LEVELS IN STINGING CATFISH HETEROPNEUSTES FOSSILIS - CHANDRA PRAKASH; ABHISHEK KUMAR; MANIRAM PRASAD; SUNIL K. SRIVASTAV; AJAI K. SRIVASTAV (International Journal of Pharma and Bio Sciences, 2015)
The present study was aimed to investigate the effects of microcystin–LR (MCLR) on the blood electrolytes of Heteropneustes fossilis. The fish were injected microcystin- LR (2.5 μg/25 g) intraperitoneally at the initiation of the experiment. Blood samples were collected and the serum calcium and phosphate levels were estimated at 1, 3, 5, 10, 15 days. There is no change in serum calcium level of microcystin-LR injected H. fossilis at day 1. The levels indicate a progressive decrease from day 3 to day 5 which tend to recover from day 10 till the end of the experiment (day 15). The first perceivable change has been noticed in serum phosphate levels, which show a decrease at day 3. This decrease progresses till day 5. Thereafter, the levels show a tendency to become normal from day 10 to day 15. It is concluded from this study that microcystin–LR exposure to the fish H. fossilis alters the blood calcium and phosphate levels of the fish, thus causing physiological disturbances which might adversely affect the normal vital functions, reproduction, growth rate and their survival in nature.